A Case for Early Language and Behavior Screening: Implications for Policy and Child Development. (March 2022) - Kaiser, Ann P.; Chow, Jason C.; Cunningham, Jennifer E.
Early language skills and prosocial behavior contribute to positive outcomes across the lifespan. Screening has improved the identification and early intervention (EI) for children with hearing loss, autism spectrum disorders, and genetically based disabilities. However, many children with significant functional impairments in language and behavior are not identified before school entry. These children have missed a critical window for EI that might have prevented or mitigated persistent developmental language impairment and challenging behaviors. The critical need for early identification of children with delays in both language and social-emotional development by proposing a preventive, universal screening approach. This approach to early screening aims to reduce the number of children on a trajectory of academic failure and social difficulties as a result of these early developmental delays.